senyawa aktif pada famili zingiberaceae sebagai anti inflamasi: studi insiliko Cycloxygenese-2 ) COX2) - Sonny Kristianto; Pramita Laksitarahmi Isrianto; Marmi Marmi; Dina Chamidah; Atta Ullah Khan (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2022)
Traditional medicine employs many ingredients that have been used for generations for treatment and are based on society's norms. These ingredients are referred to as jamu. The research aim was to determine the types and uses of medicinal plants, the active compound content, and the potential of traditional herbal medicine as a fever-lowering bio-computation. The traditional herbal formula was determined using a direct interview method combined with a purposive sampling technique in this study. We used the software for phytochemical screening and molecular docking. COX-2 was used to analyse proteins, and six ligands were used: Quercetin, Curcuminoid, Zingerone, Heyneanone, Zerumbone, and Sabinene. This study discovered 22 different types of medicinal plants in Bangselok village, East Java, Indonesia. The Zingiberaceae family is frequently used as an ingredient in herbal medicine. Ginger, Lempuyang, Bangle, Temu Mangga, Temu Putih, and Temu Giring contain flavonoid compounds. The docking results showed that Quercetin, Zingerone, Heyneanone, Zerumbone, and Sabinene ligands were attached to domain A by the control of natural COX-2 ligands, namely NAG and EDO, predicting that they could be used as an anti-inflammatory and the combination of active compounds recommended as herbal medicine.